PENGARUH MACAM MULSA ORGANIK DAN PEMANGKASAN TERHADAP HASIL TANAMAN MENTIMUN (Cucumis sativus, L.) VAR. OR GREEN 51 - Ummi Farida Fitriani; Agus Suprapto; Tujiyanta Tujiyanta (JURNAL VIGOR, 2017)
Research on the Effect of Kinds Organic Mulch and Prunning on Crop Cucumber (Cucumis sativus, L.).) Variety Or Green 51, was conducted from September until December 2016 Kebumen Village, District Pringsurat, Temanggung. The Altitude is 550 m, the soil pH 6. The method used was factorial (4x3) ware arranged in a complete randomized design with three replications. The first factor has kind of organic mulch with bamboo leaf litter mulch, straw mulch and rice husk mulch. The second factor has the pruning with the remaining 8 sections, 12 sections, and 12 main stem sections. The analysis showed wide organic mulch can improved of fresh weight per fruit, fresh weight per plant, volume fruit, dry weight of shoots and dry weight of roots. Pruning the main stem, leaving 12 sections increased fresh weight per fruit, fresh weight per plant and volume fruit. Different kinds of organic mulch at different pruning the main stem gave the same results on all parameters  observed.